Jurnal Matematika Mandiri (JMM) sebagai Inovasi Penilaian Pembelajaran Matematika SMA Kelas X - Bayu Bagus Riyandiarto; Nanda Noor Fadjrin (Limacon: Journal of Mathematics Education, 2019)
The purpose of this study is to determine the teacher's perception of the importance of the role of the assessment of mathematics learning and to develop an Jurnal Matematika Mandiri (JMM) as an innovation assessment in class X mathematics learning. the mathematics learning assessment literature continues with its production, then testing the use of the assessment is conducted. The next stage is to distribute journals in several high schools in the Cilacap Regency. Research subjects involved in this study include mathematics teachers and students of class X MIPA 2 SMA Negeri 1 Kroya. The results of the study in terms of teacher perceptions indicate that, teachers have not been able to distinguish between assessment and evaluation so that the teacher has not maximized his teaching experience using learning assessments. Based on students' responses to JMM, there are six students in category A, 11 students in category B, seven students in category C and six students in category D. In addition, giving ratings on teacher performance from the student's point of view shows that students quite like the method the teaching applied by the teacher in the class..